1989
DOI: 10.1017/s0033291700024247
|View full text |Cite
|
Sign up to set email alerts
|

Predicting relapse in schizophrenia: the development and implementation of an early signs monitoring system using patients and families as observers, a preliminary investigation

Abstract: SynopsisRecognition of prodromal symptoms of schizophrenia offers the potential of early intervention to avert relapse and re-hospitalization (Carpenter & Heinrichs, 1983). The present study investigated how a strategy to detect prodromal signs might be effectively applied in the clinical setting. A standard monitoring system was developed involving completion of a new early signs scale (ESS) measuring changes in key symptoms phenomenologically (self-report) and behaviourally (observer report). The ESS was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
217
0
8

Year Published

1993
1993
2003
2003

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 320 publications
(232 citation statements)
references
References 14 publications
7
217
0
8
Order By: Relevance
“…One welldeveloped strategy for the prevention of relapse in schizophrenia is the monitoring of prodromes or ' early signs ' of relapse (Birchwood & Spencer, 2001). Eight prospective studies of early signs (Subotnik & Neuchterlein, 1988 ;Birchwood et al 1989 ;Jolley et al 1990 ;Marder et al 1991Marder et al , 1994Tarrier et al 1991;Gaebel et al 1993 ;Jorgensen, 1998) confirm that relapse is almost always preceded by non-psychotic symptoms such as anxiety and depression, and low-level psychotic symptoms such as ideas of reference. However, the occurrence of early signs does not necessarily mean that relapse is inevitable.…”
Section: Introductionmentioning
confidence: 99%
“…One welldeveloped strategy for the prevention of relapse in schizophrenia is the monitoring of prodromes or ' early signs ' of relapse (Birchwood & Spencer, 2001). Eight prospective studies of early signs (Subotnik & Neuchterlein, 1988 ;Birchwood et al 1989 ;Jolley et al 1990 ;Marder et al 1991Marder et al , 1994Tarrier et al 1991;Gaebel et al 1993 ;Jorgensen, 1998) confirm that relapse is almost always preceded by non-psychotic symptoms such as anxiety and depression, and low-level psychotic symptoms such as ideas of reference. However, the occurrence of early signs does not necessarily mean that relapse is inevitable.…”
Section: Introductionmentioning
confidence: 99%
“…However we did not use the Jadad Scale was to exclude trials. Addington 1990 , Emsley 2004, Emsley 1999, Gaebel 2004, Heydebrand 2004, Keefe 2000, Lieberman 2005b, Perez 2003, Purdon 2000, Schooler 2003, Wang 2000, Wunderink 2003 Not randomised 36 descriptions of services 7 Bao 2005, Birchwood 1989, Clare 1994, Fisher 2001, Parlato 1999, Welch 2000, Whitwell 2000, Wieneke 2000 before and after studies 12 Addington 1999, Alanen 1994, Albiston 1998, Culberg 1998, DeHaan 1997, Fitzgerald 1998, Fresan 2001, Newton 2005, Rund 1994, Szymanski 1994, Whitehorn 1998, Yap 2001 quasi-experimental studies 3 COPE-Melbourne, TIPS 2006, Walczewski 1998 inadequate randomisation 2 McCay 2007, Mosher 1975 uncontrolled studies 13 Agius 2007, Falloon 1992, Hartmann 1974, Jenner 2001, Kadota 1992, Kauranen 2000, Keshavan 1998…”
Section: Details Of Previous Searchesmentioning
confidence: 99%
“…Low level psychotic symptoms may include suspiciousness , ideas of reference, and feelings of not tting in with others (Hirch & Jolley, 1989). Birchwood et al (1989) showed that 72% of patients had a prodrome of at least two weeks and 59% had a prodrome of four weeks or more. Hertz and Melville (1980) found 70% of patients and 93% of relatives reported changes that indicated that a relapse was imminent.…”
Section: Monitoring Prodromal Signsmentioning
confidence: 99%